2018
DOI: 10.1111/febs.14453
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy during ageing – from Dr Jekyll to Mr Hyde

Abstract: Autophagy is a ubiquitous catabolic process, which causes cellular bulk degradation through vesicular engulfment of obsolete, damaged or harmful cytoplasmic components. While autophagy regulates cellular homeostasis during development and in youth, there is mounting evidence that autophagy becomes increasingly dysfunctional with age. Recent work in Caenorhabditis elegans even suggests that late‐life dysfunctional autophagy exhibits detrimental effects that drive the ageing process. Other studies link elevated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 87 publications
0
14
0
1
Order By: Relevance
“…As a potential mechanism, interference with cell fates controlled by mTOR in response to stress and metabolic cues has been discussed 48 . Autophagy, regulated chiefly by mTORC1, is accorded a central role in the preservation of juvenile cell adaptability 48,49 since it exercises a double function as a survival mechanism in cellular stress conditions: during starvation, when mTORC1 is physiologically inhibited, autophagy regenerates basal metabolic precursors by "self-cannibalism" of cellular structures 24 . On the other hand, cellular debris such as misfolded proteins and dysfunctional organelles that can induce senescence and apoptosis is cleared by autophagy 50 .…”
Section: Discussionmentioning
confidence: 99%
“…As a potential mechanism, interference with cell fates controlled by mTOR in response to stress and metabolic cues has been discussed 48 . Autophagy, regulated chiefly by mTORC1, is accorded a central role in the preservation of juvenile cell adaptability 48,49 since it exercises a double function as a survival mechanism in cellular stress conditions: during starvation, when mTORC1 is physiologically inhibited, autophagy regenerates basal metabolic precursors by "self-cannibalism" of cellular structures 24 . On the other hand, cellular debris such as misfolded proteins and dysfunctional organelles that can induce senescence and apoptosis is cleared by autophagy 50 .…”
Section: Discussionmentioning
confidence: 99%
“…Clearance of misfolded proteins, damaged organelles and global turnover of the components of the cell takes place through autophagy [250]. Autophagy can be of three different types including microautophagy, chaperone mediated autophagy and macroautophagy [250]. Microautophagy is the normal process of engulfment of unwanted material of the cytosol in the lysosomal vesicle [251].…”
Section: Restoring Protein Homeostasis As a Novel Multifactorial Amentioning
confidence: 99%
“…Increase in AMP/ATP ratio during starvation activates AMPK and inhibits protein kinase B (Akt)/mechanistic target of rapamycin (mTOR) pathway, activating the initiation of the autophagosome formation. ROS (dihydronicotinamide-adenine dinucleotide phosphate/NADPH oxidase-induced) accumulation, PI3K/Akt/mTOR inhibition, AMPK, Beclin1, transcription factor EB (TFEB) and sirtuin 1 (SIRT1)/fork head box like protein (FOXO) activation are known pathways for inducing autophagy [250,255,256,257,258].…”
Section: Restoring Protein Homeostasis As a Novel Multifactorial Amentioning
confidence: 99%
“…Macroautophagy, hereafter referred to as autophagy, is a dynamic cellular process in which the cytoplasmic membrane structure encapsulates damaged organelles and misfolded proteins; the membrane structure then fuses with lysosomes to form autophagosomes, where the contents are degraded to maintain physiological cellular homeostasis and improve cellular functions, including survival . Previous studies have confirmed a decrease in autophagy in human OA cartilage , and the activation of autophagy increases the levels of Collagen II and Aggrecan while decreasing the expression of a disintegrin and metalloproteinase with thrombospondin motifs 5 (ADAMTS‐5) and matrix metalloproteinase‐13 (MMP‐13) in chondrocytes, which are key factors contributing to anabolism and catabolism, respectively, in cartilage .…”
Section: Introductionmentioning
confidence: 99%